Antibiotic Driven Changes in Gut Motility Suggest Direct Modulation of Enteric Nervous System - Delungahawatta, Thilini; Amin, Jessica Y.; Stanisz, Andrew M.; Bienenstock, John; Forsythe, Paul; Kunze, Wolfgang A. (Frontiers in Neuroscience, 2017)
Antibiotic-mediated changes to the intestinal microbiome have largely been assumed to be the basis of antibiotic-induced neurophysiological and behavioral changes. However, relatively little research has addressed whether antibiotics act directly on the host nervous system to produce these changes. We aimed to identify whether acute exposure of the gastrointestinal tract to antibiotics directly modulates neuronally dependent motility reflexes, ex vivo. Motility of colon and jejunum segments in a perfusion organ bath was recorded by video and alterations to neuronally dependent propagating contractile clusters (PCC), measured using spatiotemporal maps of diameter changes. Short latency (<10 min) changes to propagating contractile clusters serve as an index of putative effects on the host nervous system. Bacitracin, penicillin V and neomycin, all produced dose-dependent alterations to the velocity, frequency and amplitude of propagating contractile clusters. Most significantly, colonic PCC velocity increased by 53% (probability of superiority (PS)=87%) with 1.42 mg/ml bacitracin, 19% (PS=81%) with 0.91 mg/ml neomycin, and 19% (PS= 86%) with 3.88 mg/ml penicillin V. Colonic frequency increased by 16% (PS=73%) with 1.42 mg/ml bacitracin, 21% (PS=79%) with 0.91 mg/ml neomycin, and 34% (PS=85%) at 3.88 mg/ml penicillin V. Conversely, colonic amplitude decreased by 41% (PS=79%) with 1.42 mg/ml bacitracin, 30% (PS= 80%) with 0.27 mg/ml neomycin and 25% (PS=79%) at 3.88 mg/ml penicillin V. In the jejunum, antibiotic-specific changes were identified. Taken together, our findings provide evidence that acute exposure of the gastrointestinal lumen to antibiotics modulates neuronal reflexes. Future work should acknowledge the importance of this mechanism in mediating antibiotic-driven changes on gut-brain signaling.